Hollow micro/nanomaterials as nanoreactors for photocatalysis - Li, X.; Liu, Jian; Masters, A.; Pareek, Vishnu; Maschmeyer, T. (American Institute of Physics, 2013)
Learning from nature, one of the most prominent goals of photocatalysis is to assemble multifunctional photocatalytic units in an integrated, high performance device that is capable of using solar energy to produce “solar hydrogen” from aqueous media. By analogy with natural systems it is clear that scaffolds with multi-scale structural architectures are necessary. In this perspective, recent progress related to the use of hollow micro/nanomaterials as nanoreactors for photocatalysis is discussed. Organised, multi-scale assemblies of photocatalytic units on hollow scaffolds is an emerging area that shows much promise for the synthesis of high performance photocatalysts. Not only do improved transport and diffusion characteristics play an import role, but increased electron/hole separation lifetimes as well as improved light harvesting characteristics by the hollow structures also do so and are touched upon in this short perspective.